Selective anion-exchange properties of second-stage layered double hydroxide heterostructures - Feng, Y; Williams, G; Leroux, F; Taviot-Gueho, C; O'Hare, D (2006)
The anion-exchange properties of second-stage [Zn2Cr(OH) 6]Cl0.5(succinate)0.25·nH2O (Zn2Cr-Succ/Cl) and [Zn2Cr(OH)6]Cl 0.5(tartrate)0.25·nH2O (Zn 2Cr-Tart/Cl) materials were investigated by means of time-resolved in situ energy-dispersive X-ray diffraction (EDXRD). Selective anion-exchange reactions were observed that were a result of the segregation between organic and inorganic anions. Indeed, the reaction of Zn2Cr-Succ/Cl and Zn2Cr-Tart/Cl second-stage compounds with either fluoride or adipate anions initially occurs with preferential replacement of the hydrophilic Cl ion with F or replacement of the hydrophobic succinate or tartrate anions with adipate; this leads to the formation of new second-stage intermediates Zn 2Cr-Succ/F and Zn2Cr-Tart/F or Zn2Cr-Adip/Cl. The formation of such heterostructures offers new perspectives for LDH intercalation chemistry, particularly in the direction of multifunctional materials. © 2006 American Chemical Society.